Irradiation Performance of a Multiphase MoNbTiVZr Refractory High-Entropy Alloy: Role of Zr-Rich Phase Precipitation - Liqiu Yong; Yilong Zhong; Hongyang Xin; An Li; Dongsheng Xie; Lu Wu; Jijun Yang (Metals)
Body-centered cubic (BCC) refractory high-entropy alloys (RHEAs) demonstrate significant potential as nuclear structural materials due to their exceptional mechanical properties and radiation tolerance. While Zr-containing RHEAs often develop multiphase structures through Zr-rich phase precipitation to enhance high-temperature mechanical performance, their irradiation response mechanisms remain poorly understood. This study investigated the microstructure evolution and radiation damage behavior in equiatomic MoNbTiVZr RHEA under Au-ion irradiation at fluences of 2 × 1015, 4 × 1015, and 1 × 1016 ions/cm2. Microstructural characterization revealed that the annealed alloy primarily consisted of near-equiatomic BCC1 phase, Zr-rich BCC2 phase, (Mo,V)Zr Laves phase, and ordered Zr2C phase. Post-irradiation analysis showed distinct defect evolution patterns: the BCC1 phase developed fine dislocation loops, while the Zr-rich BCC2 and Zr2C phases exhibited dislocation clusters and dense dislocation networks, respectively. BCC1 phase exhibited the most pronounced irradiation hardening corresponding to its fine, dispersed dislocation loop characteristics. Phase separation induced by Zr precipitation reduced chemical complexity, accelerating irradiation defect evolution. These findings demonstrated that Zr-rich phase precipitation detrimentally impacted the radiation resistance of BCC-structured RHEAs, suggesting that single-phase stability should be prioritized in nuclear material design.